Performance of a New One-step Multi-mode Adhesive on Etched vs Non-etched Enamel on Bond Strength and Interfacial Morphology - Fernando de Goes, Mario; Shinohara, Mirela Sanae [UNESP]; Freitas, Marcela Santiago (Quintessence Publishing Co Inc, 2014)
Purpose: To compare microtensile bond strength (mu TBS) and interfacial morphology of a new one-step multi-mode adhesive with a two-step self-etching adhesive and two etch-and-rinse adhesives systems on enamel.Materials and Methods: Thirty human third molars were sectioned to obtain two enamel fragments. For mu TBS, 48 enamel surfaces were ground using 600-grit SIC paper and randomly assigned into 6 groups (n = 8): non-etched Scotchbond Universal [SBU]; etched SBU [SBU-et]; non-etched Clearfil SE Bond [CSE]; etched CSE [CSE-et]; Scotchbond Multi-Purpose [SBMP]; Excite [EX]. The etched specimens were conditioned with 37% phosphoric acid for 30 s, each adhesive system was applied according to manufacturers' instructions, and composite resin blocks (Filtek Supreme Plus, 3M ESPE) were incrementally built up. Specimens were sectioned into beams with a cross-sectional area of 0.8-mm(2) and tested under tension (1 mm/min). The data were analyzed with one-way ANOVA and Fisher's PLSD (alpha = 0.05). For interface analysis, two samples from each group were embedded in epoxy resin, polished, and then observed using scanning electron microscopy (SEM).Results: The mu TBS values (in MPa) and the standard deviations were: SBU = 27.4 (8.5); SBU-et = 33.6 (9.3); CSE = 28.5 (8.3); CSE-et = 34.2 (9.0); SBMP = 30.4 (11.0); EX = 23.3 (8.2). CSE-et and SBU-et presented the highest bond strength values, followed by SBMP, CSE, and SBU which did not differ significantly from each other. EX showed the statistically significantly lowest bond strength values. SEM images of interfaces from etched samples showed long adhesive-resin tags penetrating into demineralized enamel.Conclusions: Preliminary etching of enamel significantly increased bond strength for the new one-step multi-mode adhesive SBU and two-step self-etching adhesive CSE.
Keywords: self-etching adhesive; etch-and-rinse adhesive; phosphoric acid; interface; functional monomer; scanning electron microscopy